Cellular uptake and toxicity effects of silver nanoparticles in mammalian kidney cells. Issue 6 (28th October 2014) - Milić, Mirta; Leitinger, Gerd; Pavičić, Ivan; Zebić Avdičević, Maja; Dobrović, Slaven; Goessler, Walter; Vinković Vrček, Ivana
Abstract: The rapid progress and early commercial acceptance of silver‐based nanomaterials is owed to their biocidal activity. Besides embracing the antimicrobial potential of silver nanoparticles (AgNPs), it is imperative to give special attention to the potential adverse health effects of nanoparticles owing to prolonged exposure. Here, we report a detailed study on the in vitro interactions of citrate‐coated AgNPs with porcine kidney (Pk15) cells. As uncertainty remains whether biological/cellular responses to AgNPs are solely as a result of the release of silver ions or whether the AgNPs themselves have toxic effects, we investigated the effects of Ag + on Pk15 cells for comparison. Next, we investigated the cellular uptake of both AgNPs and Ag + in Pk15 cells at various concentrations applied. The detected Ag contents in cells exposed to 50 mg l −1 AgNPs and 50 mg l −1 Ag + were 209 and 25 µg of Ag per 10 6 cells, respectively. Transmission electron microscopy (TEM) images indicated that the Pk15 cells internalized AgNPs by endocytosis. Both forms of silver, nano and ionic, decreased the number of viable Pk15 cells after 24 h in a dose‐dependent manner. In spite of a significant uptake into the cells, AgNPs had only insignificant toxicity at concentrations lower than 25 mg l −1, whereas Ag + exhibited a significant decrease in cell viability at one‐fifth of this concentration. The Comet assay suggested that a rather high concentration of AgNP (above 25 mg l −1 ) is able to induce genotoxicity in Pk15 cells. Further studies must seek deeper understanding of AgNP behavior in biological media and their interactions with cellular membranes. Copyright © 2014 John Wiley & Sons, Ltd. Abstract : The rapid progress and early commercial acceptance of silver‐based nanomaterials is owed to their biocidal activity. Besides embracing the antimicrobial potential of silver nanoparticles (AgNPs), it is imperative to give special attention to the potential adverse health effects of nanoparticles owing to prolonged exposure. Here, we report a detailed study on the in vitro interactions of citrate‐coated AgNPs with porcine kidney (Pk15) cells. As uncertainty remains whether biological/cellular responses to AgNPs are solely as a result of the release of silver ions or whether the AgNPs themselves have toxic effects, we investigated the effects of Ag + on Pk15 cells for comparison.